Addressing management questions for Ngorongoro Conservation Area, Tanzania, using the Savanna modelling system - Boone, Randall B.; Coughenour, Michael B.; Galvin, Kathleen A.; Ellis, James E. (African journal of ecology, 2002)
Ngorongoro Conservation Area (NCA), in northern Tanzania, is a multiple‐use area of importance to Maasai pastoralists and wildlife conservation. We adapted the Savanna modelling system to the NCA, creating an Integrated Management and Assessment System that allows users to assess responses to alternative management actions. We used the system to conduct fifteen experiments reflecting potential management questions. Results suggest that: the distribution of rainfall throughout the year may have a greater impact on the ecosystem than its quantity; cattle may be near a carrying capacity determined not by forage limitations but because of disease risks; increasing survival and reducing disease in livestock yields greater returns than increasing birth rates; allowing livestock to graze in areas where they are currently excluded may lead to a slight increase in livestock populations, but sometimes leads to large declines in wildlife populations; few ecosystem effects were noted when households and cultivation were allowed to grow at 3% per year for 15 years; and when up to 5% of the study area was in cultivation, there were declines ≤16% in livestock and wildlife populations, except for elephants, which declined by 48%. Users may modify our experiments using tools we have developed, or address other NCA management questions. Résumé L'Aire de Conservation du Ngorongoro (NCA), au nord de la Tanzanie, est une aire multi‐usages importante pour les pasteurs Masaï et pour la conservation de la faune sauvage. Nous avons adapté le modèle SAVANNA à la NCA, créant un Système intégré de gestion et d'évaluation qui permet à ses utilisateurs d'évaluer les réponses à différentes activités de gestion. Nous nous sommes servis du modèle pour mener 15 expériences reflétant différents problèmes de gestion possibles. Les résultats suggèrent que: la distribution des chutes de pluies tout au long de l'année peut avoir un plus grand impact sur l'écosystème que leur quantité; le bétail peut être proche de la charge pondérale, déterminée non par la disponibilité de la nourriture, mais par les risques de maladies; augmenter la survie et réduire les maladies du bétail donne de meilleurs résultats que d'augmenter la natalité; permettre au bétail de pâturer dans des zones d'où il est actuellement exclu peut augmenter légèrement les populations de bétail, mais cela entraîne parfois un déclin important des populations sauvages; on a remarqué peu d'effets sur l'écosystème lorsque les foyers et leurs cultures ont été autorisés à croître de 3% par an pendant 15 ans; et lorsque 5% de l'aire étudiée ont été mis en culture, on a constaté une diminution ≤16% des populations de bétail et de faune sauvage, sauf des éléphants qui ont diminué de 48%. Les utilisateurs peuvent modifier nos expériences en se servant des outils que nous avons mis au point, ou aborder d'autres problèmes de gestion de la NCA.